2019
DOI: 10.1016/j.ygcen.2018.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Systems analysis of the liver transcriptome in adult male zebrafish exposed to the non-ionic surfactant nonylphenol

Abstract: Nonylphenol (NP) arises from the environmental degradation of nonylphenol ethoxylates. It is a ubiquitous environmental contaminant and has been detected at levels up to 167 nM in rivers in the United States. NP is an endocrine disruptor (ED) that can act as an agonist for estrogen receptors. The Adverse Outcome Pathway (AOP) framework defines an adverse outcome as the causal result of a series of molecular initiating events (MIEs) and key events (KEs) that lead to altered phenotypes. This study examined the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Finally, it has been demonstrated in zebrafish, through a transcriptomic approach, that 4-NP induced a perturbation in gene expression, compatible sponse and with a dysregulation of cell cycle. [38] In the present study, we have attempted to improve the knowledge of molecular mechanisms at the basis of 4-NP hepatotoxicity. Through the MTT viability assay, we found that the treatment with 4-NP for 24 h was cytotoxic for HepG2 cells, as it induced a reduction of more than 50% of viability at a concentration observed the highest increase of p53, a protein able to block the cell cycle in the presence of stressor compounds [39] and able to induce apoptosis when overexpressed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, it has been demonstrated in zebrafish, through a transcriptomic approach, that 4-NP induced a perturbation in gene expression, compatible sponse and with a dysregulation of cell cycle. [38] In the present study, we have attempted to improve the knowledge of molecular mechanisms at the basis of 4-NP hepatotoxicity. Through the MTT viability assay, we found that the treatment with 4-NP for 24 h was cytotoxic for HepG2 cells, as it induced a reduction of more than 50% of viability at a concentration observed the highest increase of p53, a protein able to block the cell cycle in the presence of stressor compounds [39] and able to induce apoptosis when overexpressed.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it has been demonstrated in zebrafish, through a transcriptomic approach, that 4‐NP induced a perturbation in gene expression, compatible with the development of steatosis, with an altered immune response and with a dysregulation of cell cycle. [ 38 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AESAN Scientific Committee: Available evidence in relation to the potential obesogenic activity of certain chemical compounds that may be present in foods mulation in hepatocytes, resulting in oxidative stress and alteration of the microbiota, among other demonstrated mechanisms (Chen et al, 2016) (Zhang et al, 2017(Zhang et al, , 2019b) (Jacobs et al, 2018) (Huff et al, 2019) (Buerger et al, 2019(Buerger et al, , 2020.…”
Section: Scientific Evidencementioning
confidence: 99%
“…To obtain enough differentially expressed genes suitable for systems-level analysis, a threshold qvalue of 0.4 of was applied. This q-value cut off was guided by the literature and previous articles on the study of estrogen receptor response (Irish et al 2016;Hardiman et al 2016;Dhamad et al 2016;Huff et al 2018Huff et al , 2019.…”
Section: Gene Ontology (Go) Analysismentioning
confidence: 99%